Novel coronavirus (COVID-19) infection: What a doctor on the frontline needs to know. (July 2020) - Down, Billy; Kulkarni, Sagar; Khan, Ameer Hamid Ahmed; Barker, Benjamin; Tang, Ivan
Abstract: Coronavirus disease 2019 (COVID-19) is a zoonotic respiratory infection originating from Wuhan, China. Rapidly spreading from Wuhan to all inhabited continents of the world, the World Health Organisation declared COVID-19 a pandemic on March 11, 2019. Infected patients present with fever and cough; radiological features include bilateral infiltrates on chest x-ray and computed tomography scanning. Management is supportive with oxygen supplementation, broad-spectrum antibiotics as well as careful fluid balancing. A number of drugs, both new and old, are currently in clinical trials and being used on an experimental basis in clinical practice. The COVID-19 pandemic is the greatest worldwide public health crisis of a generation, and has led to seismic political, economic and social changes. This review provides an overview of COVID-19 for junior doctors who find themselves on a new frontline of healthcare. Highlights: Coronavirus disease 2019 is a zoonotic respiratory infection that rapidly spread from China to become a pandemic. The most common symptoms are cough, fever and shortness of breath; infection typically produces mild symptoms. A minority of patients have severe symptoms, such as respiratory failure, which requires hospital admission and even intensive care unit admission. Guidelines suggest that the management of coronavirus disease 2019, in most cases, is supportive Several agents, such as hydroxychloroquine, azithromycin and remdesivir are currently under investigation as treatment for the disease.